Pulsatile dynamics propagate crystalline order in the developing Drosophila eye - Couturier, Lydie; Luna-Escalante, Juan; Mazouni, Khallil; Mestdagh, Claire; Phan, Minh-Son; Tinevez, Jean-Yves; Schweisguth, François; Corson, Francis (bioRxiv, 2025)
Pattern formation in developing tissues often involves self-organization guided by positional information. In most tissues, however, its dynamics, and therefore the underlying logic, remain unknown. Examining self-organized patterning of the fly eye, we combine experiments and modeling to elucidate how rows of light-receiving units emerge in the wake of a traveling differentiation front to form a crystal-like array. Live imaging of the proneural factor Atonal reveals unanticipated oscillations at the front, which are produced by the successive activation of two distinct enhancers and associated with pulsatile Notch signaling. Our observations are inconsistent with current models of eye patterning, whereby each row of differentiating cells provides a negative template for the next. Instead, they inform a new relay model in which transient Notch signaling from differentiating cells provides a positive template for the onset of differentiation two rows ahead, conveying both temporal and spatial information to propagate oscillations and crystal-like order.